Low energy, high intensity metal ion implantation method for deep dopant containing layer formation; Surface and Coatings Technology; Vol. 355 - Ryabchikov A. I. Aleksandr Ilyich; Shevelev A. E. Aleksey Eduardovich; Sivin D. O. Denis Olegovich; Ivanova A. I. Anna Ivanovna; Medvedev V. N. Vladislav Nikolaevich (2018, 2018)
Title screen